Abuso sexual infantil: Conhecimento do enfermeiro sobre o seu papel no acolhimento das vítimas e na notificação de casos - Pedroso, Vera Lucia Barreto (2013)
This study presents data on the knowledge of twenty nurses working in public a municipality in the Metropolitan Region of Curitiba about sexual abuse against children and adolescents. The age of participants ranged from 27 to 55 years, with an average of 17 years of training in nursing and 7.2 years of dedication to public service at City Hall. For data collection, two focus groups were conducted with participants, addressing six themes through a structured interview, which allowed the emergence of the following categories of data: What is sexual abuse against children and adolescents, the role of nurses against the sexual abuse, indicators of sexual abuse, sexual abuse consequences for the victim, because the sexual abuse occurs and How to protect children from sexual abuse. Data analysis showed that the participants' knowledge about what sexual abuse is empirical, evidencing the lack of information during their training. It was observed that the role of the nurse in the sexual abuse is a topic generating anxiety as participants reported a lack of support from relevant bodies for notification, as secrecy is the name of the notifier, is the lack of information necessary to continued monitoring of cases . Another important issue reported by participants was the fear of making the required notification, due to possible retaliation by alleged offenders against professional notifies the nurse that takes up the use of anonymous tips to break the cycle of sexual violence against children. Participants also showed low level of information as indicators of sexual abuse, sexual abuse causes, consequences of sexual abuse and sexual abuse prevention, needing more training practices on prevention that are recommended to professional nursing.